Uma contribuição da contabilidade momentum para a contabilidade gerencial: um estudo de caso - Morcelli, Celso Amorim (2013)
The present research aimed to apply in a Brazilian company in the educational segment, SENAC São Paulo, the indices developed by Eric Melse, in his article published in 2004 in the journal Balance Sheet using the concepts from accounting with the title momentum Accounting in three dimensions: the case for momentum, where he analyzed the data of company Robert Half International Incorporated during the period from 1987 to 2002, the research assessed the information generated by the momentum accounting as a tool of management accounting through the application of case study and justifies itself as possibility to present itself as a new tool of managerial decision-making, given its benefit to bring a different way of analyzing companies, adding new facts for the analysis of financial managers and thus collaborating with the decision-making is long or short term. The research work was conducted exploratory qualitatively. The data were collected through the company's accounting statements in the statement of the last 10 years from 2002 to 2012. The research concluded that the indices developed by Eric Melse Momentum accounting can contribute to managerial accounting